Occupational contact allergy of construction workers in Greece: Trends during 2009–2018. (27th September 2021) - Gregoriou, Stamatios; Anagnostou, Periklis; Mastraftsi, Styliani; Platsidaki, Eftychia; Tsimpidakis, Antonis; Chatzidimitriou, Eleni; Kontochristopoulos, George; Katoulis, Alexandros; Nicolaidou, Electra; Stratigos, Alexandros; Rigopoulos, Dimitrios
Abstract: Background: Recent trends in the sensitization of construction workers show a decrease in potassium dichromate and an increase in epoxy resin sensitization. Objectives: To present the trends of occupational contact allergy of construction workers in Greece from 2009 to 2018. Methods: We retrospectively reviewed the files of patients with eczema patch tested in our Contact Dermatitis Clinic who were construction workers. Results: A total of 191 construction workers initially reported contact dermatitis. Of these, 138 had occupation‐relevant allergic contact dermatitis (ACD) or irritant contact dermatitis (ICD). All patients were men. After being patch tested, 98 (71.0%) were diagnosed with ACD and 40 with ICD. Median duration of occupation till onset of ACD was 2 years (interquartile range [IQR] 0.8–7). The hands were the most common location for ACD (73.5%), followed by the trunk (39.8%), the legs (38.8%), and the face (11.2%). Of the patients, 74.6% had lesions affecting multiple body sites. Potassium dichromate (67%) was the most frequent allergen, followed by thiuram mix (37.4%) and cobalt chloride (31.8%). Sensitization to epoxy resins was lower (12.1%). Conclusion: The sensitization pattern of Greek construction workers does not follow the trends in Central or Northern Europe, rather sharing attributes with less industrialized countries.